Case Report: UMOD gene mutation and phenotypic overlap with REN in autosomal dominant tubulointerstitial kidney disease - Xu, Jingying; Chen, Enhui; Shi, Wen; He, Wenhui; Yu, Dongrong; Li, Xianfa (Frontiers in Genetics, 2025)
Autosomal dominant tubulointerstitial kidney disease (ADTKD) is a rare monogenic kidney disorder characterized by progressive tubular atrophy and interstitial fibrosis. It is primarily associated with pathogenic variants in genes such as UMOD (uromodulin), REN (renin), MUC1 (mucin 1), and HNF1B (hepatocyte nuclear factor 1-beta). We report a unique Chinese case of ADTKD-UMOD in a patient carrying a UMOD gene mutation. The clinical presentation was complex: in addition to the classic features of UMOD mutations (hyperuricemia and gout), the patient exhibited endocrine and metabolic abnormalities typically linked to REN gene defects (ADTKD-REN), including anemia, hypotension, and hyporeninemic hypoaldosteronism. However, renal biopsy and genetic testing ultimately confirmed the diagnosis as ADTKD caused by a heterozygous missense mutation in UMOD gene.